Equivalence of cell survival data for radiation dose and thermal dose in ablative treatments: analysis applied to essential tremor thalamotomy by focused ultrasound and gamma knife. (19th May 2017) - Schlesinger, D.; Lee, M.; ter Haar, G.; Sela, B.; Eames, M.; Snell, J.; Kassell, N.; Sheehan, J.; Larner, J. M.; Aubry, J. -F.
Abstract: Thermal dose and absorbed radiation dose have historically been difficult to compare because different biological mechanisms are at work. Thermal dose denatures proteins and the radiation dose causes DNA damage in order to achieve ablation. The purpose of this paper is to use the proportion of cell survival as a potential common unit by which to measure the biological effect of each procedure. Survival curves for both thermal and radiation doses have been extracted from previously published data for three different cell types. Fits of these curves were used to convert both thermal and radiation dose into the same quantified biological effect: fraction of surviving cells. They have also been used to generate and compare survival profiles from the only indication for which clinical data are available for both focused ultrasound (FUS) thermal ablation and radiation ablation: essential tremor thalamotomy. All cell types could be fitted with coefficients of determination greater than 0.992. As an illustration, survival profiles of clinical thalamotomies performed by radiosurgery and FUS are plotted on a same graph for the same metric: fraction of surviving cells. FUS and Gamma Knife have the potential to be used in combination to deliver a more effective treatment (for example, FUS may be used to debulk the main tumour mass, and radiation to treat the surrounding tumour bed). In this case, a model which compares thermal and radiation treatments is valuable in order to adjust the dose between the two.